Communicating Fatwa: Strategic Public Engagement By MUI SULSEL - Firdaus Muhammad; Sanusi, Hartinah; Khaerunnisa; Muhammad Alamsyah (Jurnal Dakwah Tabligh, 2025)
This study explores the public communication strategies employed by the South Sulawesi branch of the Indonesian Ulema Council (MUI) to disseminate Fatwa No. 1 of 2021, which prohibits almsgiving to street children and beggars in public spaces. In a rapidly evolving media landscape, the effective communication of religious edicts requires adaptive and contextually grounded approaches. Using an explorative qualitative design, data were gathered through in-depth interviews with MUI leaders, government officials, and community members, along with observations of digital and mass media content. Analysis employed the Miles and Huberman model and pragmatic-ethical discourse analysis, particularly focusing on six Qur’anic qaulan principles. The study found that the fatwa’s reach was achieved through two core strategies: strategic media engagement and collaboration with local authorities. Islamic communication ethics—especially qaulan sadidan (truthful speech) and qaulan layyinan (gentle speech)—were essential in building legitimacy and persuasive impact. The findings underscore the vital role of religious institutions as ethical communicators and agents of social change.